Estudo da ação de Maytenus ilicifolia encapsulada em microesferas de alginato em modelo in vivo de úlcera péptica - Moda, Marlon (2024)
Peptic ulcer is a recurrent chronic disease that represents a typical condition of the civilized world due to lifestyle and dietary habits. The symptoms are characterized by pain or burning in the epigastrium and may be associated with dyspepsia, nausea, and early satiety. Studies suggest herbal medicines with beneficial effects on ulcers or gastritis through multiple mechanisms including antioxidant activity, stimulation of mucosal epithelial proliferation, inhibition of acid secretion, increased mucus production, culminating in the inhibition of the inflammatory process. In Brazil, a herbal medicine that demonstrates great efficacy in gastrointestinal disorders is derived from the plant genus Maytenus spp., with extracts obtained from Maytenus ilicifolia leaves being the most promising and already commercialized in the form of capsules or solution. In order to enhance the therapeutic effect, associating a herbal medicine with a resorbable biomaterial has been gaining importance to achieve results in a shorter treatment time, maximizing the regenerative and functional process of the affected tissue or organ. Alginate is a natural polymeric biomaterial obtained from algae and represents a promising alternative as an adjuvant in experimental therapies. This work was based on the development of a prolonged release system with alginate microspheres associated with M. ilicifolia extract. The microspheres with or without M. ilicifolia were characterized by SEM, TG, DSC, FTIR, UV-VIS. In the release assay, it was identified that 20mg of microspheres released up to 5,2mg of M. ilicifolia in 48h in a gastric acid mimetic environment. After being subjected to experimental gastritis, Wistar rats were treated for 06 days in different experimental groups containing alginate microspheres with and without M. ilicifolia. Comparative macro and microscopic anatomopathological presentation between groups demonstrated an initial process of ulcer remission, with emphasis on the preservation of gastric pits and glands in the group treated with microspheres loaded with M. ilicifolia. The natural compound developed here proved to be effective in a short-term experimental treatment in the murine model, which highlights its potential as an alternative therapeutic agent in cases of gastritis and/or peptic ulcers